EFFECTS OF ORAL SODIUM BICARBONATE SUPPLEMENTATION ON NUTRITIONAL STATUS OF PATIENTS UNDERGOING MAINTENANCE HEMODIALYSIS - RAFIQ, A; ARSHAD, AR (Biological and Clinical Sciences Research Journal, 2023)
To determine the oral sodium bicarbonate supplementation effects on nutritional status of patients undergoing maintenance hemodialysis. In a Medicine department at Combined Military Hospital, Peshawar, a case-control study was carried on “14-October 2021 to 14-April 2022”. It enrolled patients of ESRD on MHD with low serum bicarbonate levels. Patients were allocated into two groups: an experimental group receiving oral sodium bicarbonate and a control group receiving standard care. Parameters such as mid-thigh circumference, serum bicarbonate, and serum albumin were assessed at baseline and after 3 months, with statistical analysis performed using an independent sample t-test. The intervention group had a notable elevation in serum bicarbonate levels (20.87±1.58 mmol/l) as compared to the control group (18.73±2.38 mmol/l) (P = 0.0001). Furthermore, it was observed that the intervention group had a noteworthy elevation in serum albumin levels after 3 months (4.40±0.28 g/l), as compared to the control group (3.77±0.30 g/l) (P = 0.0001). Additionally, there was a statistically significant rise in the average mid-thigh circumference among participants in the intervention group during the third month, in comparison to those of the control group (41.20±1.70 vs. 39.74±1.27 cm; P = 0.001). Oral sodium bicarbonate supplementation in patients on maintenance hemodialysis significantly increased serum bicarbonate level, serum albumin level and mid-thigh size.